PENGARUH BRANDING STRATEGY, SERVICE QUALITY, DAN DIGITAL MARKETING TERHADAP CUSTOMER LOYALTY MINISO - Silvie Karina Karina; M. Hafizh Irzain Akmal; Ibrahim Zarkasi; Julia Nur Wijayanti; I Made Bagus Dwiarta (Media Mahardhika, 2026)
The competition in Indonesia’s retail industry has become increasingly intense as consumer lifestyle demands continue to evolve. This dynamic has created greater challenges in fostering customer loyalty at PT Miniso Lifestyle Trading Indonesia. This study aims to examine the effects of Branding Strategy, Service Quality, and Digital Marketing on Customer Loyalty at PT Miniso Lifestyle Trading Indonesia (Miniso). The study employs a quantitative research approach using a survey method. Data were collected through the distribution of 120 questionnaires to Miniso customers who had made at least two purchases, using an accidental sampling technique. The data were analyzed using multiple linear regression, supported by validity and reliability tests, classical assumption tests, and hypothesis testing. The findings reveal that, individually, Branding Strategy, Service Quality, and Digital Marketing each have a significant positive effect on Customer Loyalty. Among these variables, Branding Strategy exerts the strongest influence. Furthermore, the results of the F-test indicate that Branding Strategy, Service Quality, and Digital Marketing simultaneously have a significant effect on Customer Loyalty at PT Miniso Lifestyle Trading Indonesia. These findings highlight that improving service quality, supported by a strong branding strategy and the effective implementation of digital marketing, can substantially enhance customer loyalty. This study is expected to serve as a valuable reference for companies in developing business strategies and strengthening customer loyalty.